2020
DOI: 10.1080/20008198.2020.1717155
|View full text |Cite
|
Sign up to set email alerts
|

Help in hand after traumatic events: a randomized controlled trial in health care professionals on the efficacy, usability, and user satisfaction of a self-help app to reduce trauma-related symptoms

Abstract: Olff (2020) Help in hand after traumatic events: a randomized controlled trial in health care professionals on the efficacy, usability, and user satisfaction of a self-help app to reduce trauma-related symptoms,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 43 publications
2
42
1
4
Order By: Relevance
“…Identifying specific risk factors that may moderate the mental health impact of the COVID-19 pandemic can help inform prevention programs and psychosocial interventions (Duan & Zhu, 2020 ; Olff et al, 2019 ; Van Der Meer, Bakker, Van Zuiden, Lok, & Olff, 2020 ). Lack of social support is one of the most well-established risk factors for unfavourable outcomes after trauma (e.g.…”
mentioning
confidence: 99%
“…Identifying specific risk factors that may moderate the mental health impact of the COVID-19 pandemic can help inform prevention programs and psychosocial interventions (Duan & Zhu, 2020 ; Olff et al, 2019 ; Van Der Meer, Bakker, Van Zuiden, Lok, & Olff, 2020 ). Lack of social support is one of the most well-established risk factors for unfavourable outcomes after trauma (e.g.…”
mentioning
confidence: 99%
“…Os Apps para os Transtornos de Ansiedade 33,51,53 e relacionados com o uso de Substâncias Psicoativas, 28,36 dentre os três principais quadros psiquiátricos presentes no Estudo de Carga de Doença, 56 foram encontrados em pouca quantidade nas buscas, indicando uma lacuna a ser preenchida com a construção para essas condições. Os Apps para TEPT 10,18,20,48,50 se mostraram presentes, porém, três dos cinco artigos eram direcionados ao mesmo App móvel com foco em veteranos de guerra dos EUA.…”
Section: Resultados Resultados Resultados Resultadosunclassified
“…Apps are available to manage PTSD symptoms, yet most have not been evaluated in randomised controlled trials. The exceptions are PTSD Coach, which has demonstrated efficacy (Kuhn et al, 2017 ; Sander et al, 2020 ), whilst SUPPORT Coach has not (van der Meer, Bakker, Zuiden, Lok, & Olff, 2020 ). CBT for PTSD delivered over the telephone achieved significant reductions in PTSD symptomatology in one clinical trial (DuHamel et al, 2010 ), and treatment via video-conferencing has been found to be acceptable to patients (Ashwick, Turgose & Murphy, 2019 ).…”
Section: Introductionmentioning
confidence: 99%